Stereoselective total synthesis of (3Z)- and (3E)-elatenynes - Kwak, Soo Yeon; Shin, Iljin; Jang, Hongjun; Park, Youngjik; Lim, Seongju; Lee, Dongjoo; Kim, Hyoungsu; Kim, Deukjoon (RSC Advances, 2023)
We describe here the highly stereoselective total synthesis of the Laurencia C15 acetogenins (3Z)- and (3E)-elatenynes having a 7,12-dibromo-6,9-cis-10,13-cis adjacent bis-tetrahydrofuran (THF) core. The present synthesis features a highly stereoselective, protecting group-dependent, chelate-controlled intramolecular amide enolate alkylation (IAEA) for the synthesis of key intermediate 7-hydroxy-6,7-cis-6,9-cis-THF intermediate 10, deployment of the sequential ate complex (n-BuLi/DIBAL-H) reduction/Keck allylation/cross metathesis (CM) protocol for the stereoselective introduction of the C(10)-C(15) unit, a sequential Sharpless asymmetric dihydroxylation (SAD)/intramolecular Williamson etherification for the construction of the 10,13-cis-THF ring, and a modified Nakata chloromethanesulfonate-mediated SN2 displacement for the 7,12-dibromo functionality. Furthermore, our strategy based on chelate-controlled IAEA methodology would provide access to any member of the C15 adjacent bis-THF acetogenin class.
Keywords: Acetogenins; Amide enolates; Ate complex; Enolate alkylation; Protecting group; Stereo-selective; Synthesis features; Tetra-hydrofuran; Tetrahydrofurans; Total synthesis